Dying to eat : cross-cultural perspectives on food, death, and the afterlife - Cann, Candi K. (Material worlds., 2018)
Food has played a major role in funerary and memorial practices since the dawn of the human race. In the ancient Roman world, for example, it was common practice to build channels from the tops of graves into the crypts themselves, and mourners would regularly pour offerings of food and drink into these conduits to nourish the dead while they waited for the afterlife. Funeral cookies wrapped with printed prayers and poems meant to comfort mourners became popular in Victorian England; while in China, Japan, and Korea, it is customary to offer food not only to the bereaved, but to the deceased, with ritual dishes prepared and served to the dead. Dying to Eat is the first interdisciplinary book to examine the role of food in death, bereavement, and the afterlife. The contributors explore the phenomenon across cultures and religions, investigating topics including tombstone rituals in Buddhism, Catholicism, and Shamanism; the role of death in the Moroccan approach to food; and the role of funeral casseroles and church cookbooks in the Southern United States. This innovative collection not only offers food for thought regarding the theories and methods behind these practices but also provides recipes that allow the reader to connect to the argument through material experience. Illuminating how cooking and corpses both transform and construct social rituals, Dying to Eat serves as a fascinating exploration of the foodways of death and bereavement.